Enhancing Scientific Research and Paper Writing Processes by Integrating Artificial Intelligence Tools - Jadán-Guerrero, Janio (2024)
This article provides a systematic guide for integrating Artificial Intelligence (AI) into many facets of scientific writing process. By analyzing various AI platforms that facilitate efficient topic identification, the formulation of investigative questions, the analysis of previous literature, data processing, structuring and presentation of manuscripts, the successful case of a training program implemented at a university in Ecuador. This initiative involved 84 academics, of which 66 managed to complete their scientific articles, with 35 of these works accepted at a recognized scientific conference. This case highlights the relevance of a deep understanding of the potential of AI to complement and enhance human research and writing capabilities. It seeks to provide an integrative approach to scientific research that optimizes the benefits of this emerging technology. This research emphasizes the need to promote writing where ethics and originality standards are the priority, thus ensuring the integrity and authenticity of the knowledge created in the scientific community.